Simulation science : first International Workshop, SimScience 2017, Göttingen, Germany, April 27-28, 2017, Revised selected papers /: first International Workshop, SimScience 2017, Göttingen, Germany, April 27-28, 2017, Revised selected papers. (2018) - Unknown
No abstract available